Ketimpangan Moral dalam Praktik Pertambangan di Indonesia: Kritik Antroposentris dan Rekonstruksi Etika Biosentris - Satria Pramuja; Elvira Purnamasari (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
Indonesia is recognized as a country with abundant mineral resources; however, the expansion of the mining sector has generated multidimensional moral inequality, encompassing an imbalance in economic benefit distribution between corporations and local communities, disregard for the intrinsic value of nature, and the marginalization of affected communities from decision-making. The dominance of the anthropocentric paradigm, which places humans as the center of value, is the root cause of this problem. This study aims to analyze moral inequality in Indonesia's mining practices, examine the anthropocentric paradigm in natural resource management, and formulate biocentric ethics as a just alternative. A qualitative approach with library research method was employed, collecting data from national scientific journals, official government reports, and environmental ethics literature, analyzed descriptively-critically through content analysis technique. Findings reveal three interrelated dimensions of moral inequality: inequality in benefit and burden distribution, inequality in recognizing the intrinsic value of nature, and inequality in participatory decision-making. A reconstruction of biocentric ethics grounded in the principles of non-maleficence, noninterference, fidelity, and restitutive justice offers a comprehensive value framework to address ecological moral deficits. This study concludes that a paradigmatic transformation from anthropocentrism to biocentrism, through Free Prior and Informed Consent implementation, the polluter pays principle, and care ethics-based governance, is a fundamental step toward ethical and sustainable mining practices.